PARACHUTING - BUNGEE - MENTAL STRAIN WITH DISSIMILAR CARDIAC AND METABOLIC IMPACT. (April 2021) - Kisters, Klaus; Moser, M.; Opresnik, S.; Seibert, F.; Porta, S.
Abstract : Objective: Parachuting and bungee jumping result in heavy mental strain with dissimilar cardiac and metabolic impact. In addition changes in blood pressure values and electrolyte metabolism may occur. Therefore it was of interest to study blood pressure and ionized magnesium values as stress markers. Design and method: Out of 100 microlitres of capillary blood from 23 parachuters and of 15 bungee jumpers sampled before and after the jump, blood glucose and ionized magnesium concentrations were determined by a NOVA Phox-M device, distributed by TECOM, Austria. Blood pressure values were measured by Beurer Instrumentation, Ulm, Germany. Results: 1. Parachuting: Sytolic and diastolic blood pressure values increased significantly after the jump (p < 0.01). Heart rate did not change significantly. Blood glucose and ionized magnesium values decreased significantly from initially high normal values (p < 0.01). 2. Bungee jumping: Also no difference in heart rate, but a slight fall in systolic and a significant fall in diastolic blood pressure values after the jump were noted (p < 0.01). Blood glucose increased from already high basal levels and ionized magnesium values decreased significantly (p < 0.01). Conclusions: Outright stress determines the sympathoadrenal anticipation, epinephrine challenge should be not dissimilarly high. However, a longer anxiety period during the para-jump proceedings could lead to time dependent contrary reactions in blood pressure, magnesium and glucose levels, all of them stress markers of different sensibility. Taken together: Mental stress has a high impact upon metabolism. Cardiovascular and metabolic markers have a different time course and reaction to workload intensity. High mental stress intensity and prolonged strain duration lead in both stress models to a decline in ionized magnesium concentrations. Ionized magnesiumconcentrations correlate to other stress markers, e.g. like pCO2 as an indicator of breathing frequency before the jump (hyperventillation). Decreased magnesium concentration before stress have to be avoided. Blood pressure has to be controlled under stress conditions.